Birdsong memory and the brain: In search of the template. (March 2015) - Bolhuis, Johan J.; Moorman, Sanne
Highlights: Songbirds learn to sing much like human infants acquire speech. The neural substrate of tutor song memory is located in the caudomedial pallium. There are intricate connections between auditory regions and the song system that might be important for song learning. Song learning-related neural activation is lateralised. Sleep is important for birdsong learning. Abstract: In his pioneering research on the neural mechanisms of filial imprinting, Gabriel Horn has gone a long way to fulfilling Karl Lashley's dream of finding the 'engram' or memory trace in the brain. Here we review recent research into the engram(s) of song learning in songbirds, particularly zebra finches. When juvenile songbirds learn their songs from a tutor, they form and alter a central representation of the tutor song, known as the 'template'. Secondary auditory regions in the caudal medial pallium are likely to contain the neural substrate for the representation of tutor song, but the roles of the different regions remain to be elucidated. Female zebra finches do not sing, but nevertheless form an auditory memory of their father's song, for which the neural substrate is located in the caudomedial pallium. In males that are learning their songs, there is continual interaction between the secondary auditory regions and sensorimotor regions, similar to the interaction between Broca's and Wernicke's areas in human infants acquiring speech and language.